Mikrostruktur dan Karakterisasi Sifat Mekanik Lapisan Cr3C2-NiAl-Al2O3 Hasil Deposisi Dengan Menggunakan High Velocity Oxygen Fuel Thermal Spray Coating - Edy Riyanto; Budi Prawara (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2010)
Surface coating processing of industrial component with thermal spray coatings have been applied in many industrial fields. Ceramic matrix composite coating which consists of Cr3C2-Al2O3-NiAl had been carried out to obtain layers of material that has superior mechanical properties to enhance component performance. Deposition of CMC with High Velocity Oxygen Fuel (HVOF) thermal spray coating has been employed. This study aims to determine the effect of powder particle size on the microstructure, surface roughness and hardness of the layer, by varying the NiAl powder particle size. Test results show NiAl powder particle size has an influence on the mechanical properties of CMC coating. Hardness of coating increases and surface roughness values of coating decrease with smaller NiAl particle size.